THE ROLE OF THE SOCIAL SERVICE OF THE DAP POVERTY ALLEVIATION IN KUANTAN SINGINGI REGENCY - Emilda Rosita; Sitti Rahmah (Indonesian Journal of Social Sciences, Policy and Politics, 2025)
This study aims to examine the role of Social Services in poverty alleviation in Kuantan Singingi Regency. By referring to aspects of education, facilitation and social welfare. This study identifies policies and programs implemented by the Social Service to improve the quality of life of the community. The method used in this study is qualitative descriptive. The method of data collection is through observation, interviews and documentation. The results of the study show that the Kuantan Regency Social Service has implemented several education and social protection programs aimed at meeting the basic needs of the poor. The community believes that despite the progress made through the Social Service program, there is a need to increase transparency, accountability, and community participation. To increase the effectiveness of poverty alleviation programs, the Social Service needs to strengthen the data collection system, collaboration between agencies, and increase community participation in the program planning and evaluation process